Associations between source of information about sex and sexual health outcomes in Britain: findings from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). Issue 3 (5th March 2015) - Macdowall, Wendy; Jones, Kyle G; Tanton, Clare; Clifton, Soazig; Copas, Andrew J; Mercer, Catherine H; Palmer, Melissa J; Lewis, Ruth; Datta, Jessica; Mitchell, Kirstin R; Field, Nigel; Sonnenberg, Pam; et al.
Abstract : Objectives: To examine variation in source of information about sexual matters by sociodemographic factors, and associations with sexual behaviours and outcomes. Design: Cross-sectional probability sample survey. Setting: British general population. Participants: 3408 men and women, aged 17–24 years, interviewed from 2010–2012 for third National Survey of Sexual Attitudes and Lifestyles. Main outcome measures: Main source of information (school, a parent, other); age and circumstances of first heterosexual intercourse; unsafe sex and distress about sex in past year; experience of sexually transmitted infection (STI) diagnoses, non-volitional sex or abortion (women only) ever. Results: Citing school was associated with younger age, higher educational level and having lived with both parents. Citing a parent was associated, in women, with lower educational level and having lived with one parent. Relative to other sources, citing school was associated with older age at first sex (adjusted HR 0.73 (95% CI 0.65 to 0.83) men, 0.73 (0.65 to 0.82) women), lower likelihood of unsafe sex (adjusted OR 0.58 (0.44 to 0.77) men, 0.69 (0.52 to 0.91) women) and previous STI diagnosis (0.55 (0.33 to 0.91) men, 0.58 (0.43 to 0.80) women) and, in women, with lower likelihood of lack of sexual competence at first sex; and experience of non-volitional sex, abortion and distress about sex. Citing a parent was associated with lower likelihood of unsafe sex (0.53 (0.28 to 1.00) men; 0.69 (0.48 to 0.99) women) and, in women, previous STI diagnosis. Conclusions: Gaining information mainly from school was associated with lower reporting of a range of negative sexual health outcomes, particularly among women. Gaining information mainly from a parent was associated with some of these, but fewer cited parents as a primary source. The findings emphasise the benefit of school and parents providing information about sexual matters and argue for a stronger focus on the needs of men.